2015
DOI: 10.3758/s13420-014-0166-6
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli with identical contextual functions taught independently become functionally equivalent

Abstract: A novel learning process that does not require stimulus associations was explored in humans. The hypothesis was that two contextual stimuli taught in separate settings, with different stimuli, become equivalent if they accomplish identical functions with regard to the relations between the stimuli presented with them. The procedure consisted of : (a) first teaching an AB conditional discrimination (e.g., match A1 to B1 and A2 to B2) and then teaching a second-order XAB conditional discrimination in which X1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The tests presented in Phase 1 demonstrated that X1 and X2 became generalized contextual cues for maintaining and reversing new conditional discriminations. These results replicated those of previous studies (Pérez-González et al, 2014;Pérez-González et al, 2015;Pérez-González & Martínez, 2007;. The tests presented in Phase 2 suggest that the training provided in Phase 1 also made of X1 and X2 cues for equivalence and nonequivalence.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The tests presented in Phase 1 demonstrated that X1 and X2 became generalized contextual cues for maintaining and reversing new conditional discriminations. These results replicated those of previous studies (Pérez-González et al, 2014;Pérez-González et al, 2015;Pérez-González & Martínez, 2007;. The tests presented in Phase 2 suggest that the training provided in Phase 1 also made of X1 and X2 cues for equivalence and nonequivalence.…”
Section: Discussionsupporting
confidence: 87%
“…Our general strategy consisted of demonstrating that two stimuli pretrained as contextual cues for equivalence and nonequivalence-instead of for sameness and opposition-can control the same type of derived responding as SAME and OPPOSITE did in RFT studies. In Phase 1, a stimulus X1 was pretrained as a cue for maintaining previously trained conditional discriminations, and a stimulus X2 was pretrained as a cue for reversing those discriminations (Pérez-González, Álvarez, Calleja, & Fernández, 2014;Pérez-González, Díaz, Fernández-García, & Baizán, 2015;Pérez-González & Martínez, 2007;. This pretraining potentially makes of X1 and X2 cues for equivalence and nonequivalence (see Pérez-González et al, 2014;.…”
mentioning
confidence: 99%
“…Consequently, the processes underlying apparent AARR in accordance with sameness and opposition have, arguably, not been properly analyzed, even though 30 years have passed since the first study on this topic. Recently, we offered an alternative account of apparent AARR in accordance with sameness and opposition based on contextual control over equivalence and nonequivalence (Alonso‐Álvarez & Pérez‐González, ; see also Lynch & Green, ; Meehan & Fields, ; Pérez‐González, Álvarez, Calleja, & Fernández, ; Pérez‐González, Díaz, Fernández‐García, & Baizán, ; Pérez‐González & Martínez, ; Pérez‐González & Serna, ; Serna & Pérez‐González, ) and responding by exclusion (e.g., Johnson & Sidman, ; Stromer & Osborne, ). We explained apparent AARR in accordance with sameness and opposition as follows: Training Same as a cue for selecting comparisons identical to the samples (e.g., matching a short line to a short line, and a long line to a long line) could establish Same as a cue for equivalence, because identity matching and equivalence usually occur in the same contexts (Sidman, ).…”
mentioning
confidence: 99%
“…Protocols are designed to establish and strengthen behaviors that lead to attachment and participatory behaviors and include descriptions of how to shape adult proximity and interaction, shape facial expressions and voices to have a reinforcing value through a combination of operant and respondent pairing contingencies (Greer, Singer-Dudek, & Gautreaux, 2006; Nuzzolo-Gomez, Leonard, Ortiz, Rivera-Valdes, & Greer, 2002; Shillingsburg, Hollander, Yosick, Bowen, & Muskat, 2015). Other protocols teach the essential tact repertoires for naming, categorizing, and describing the features and functions of objects that are subsequently used to teach rudimentary social/conversational skills (Greer, Stolfi, Chavez-Brown, & Rivera-Valdez, 2005; Greer, Stolfi, & Pistoljevic, 2007; Miguel, Petursdottir, Carr, & Michael, 2008; Pérez-González, Díaz, Fernández-García, & Baizán, 2015; Pérez-González, Garcia-Asenjo, Williams, and Carnerero, 2007; Pérez-González, Hervzlikowicz, and Williams, 2008; Williams, Carnerero, & Pérez-González, 2006; Williams, Pérez-González, and Vogt, 2003).…”
Section: Progression Of Instructional Deliverymentioning
confidence: 99%